Victim behavior of crime victims - Головкін, Богдан Миколайович (Problems of legality, 2016)
The article tells about phenomenon of victim’s behavior in commission of crimes, found its genesis and describes basic models of such behavior. Victim behavior is the person acts or omissions that led to her selection as offering and were the reason for commit the crime in a specific situation. The gist of victim’s behavior is dangerous for person behavior in situations of interaction with the criminal. Dangerous of such behavior is allowing for the location, time and scenarios before committing a crime, or at the time a criminal assault. Victim’s behavior attracts attention of the criminal, causes the choice of victim, become a pretext for committing a crime against the person who was raised in a vulnerable situation. The shape of this behavior is mainly careless. Much less people are deliberately exposed to unlawful acts. For the moment the emergence of victim behavior prior commission the offense or appears at the moment of interaction between the offender and the victim. Similarly victim behavior can deployment and change in the process of committing a crime. Display of victim’s behavior are relatively few; mostly of them are typical.